Analisis penerimaan pajak barang dan jasa tertentu serta kontribusinya pada pendapatan asli daerah di Badan Pendapatan Daerah Kota Manado - Tatamang, Claudia Sherlyka; Pangerapan, Sonny; Mintalangi, Syermi S. E. (Riset Akuntansi dan Portofolio Investasi, 2025)
The Specific Goods and Services Tax (PBJT) plays a strategic role in strengthening Local Own-Source Revenue (PAD), especially in economically dynamic regions such as Manado City. This study examines the effectiveness of PBJT collection, its contribution to PAD, and the implementation of tax optimization strategies by the Regional Revenue Agency (BAPENDA). Using a qualitative case study approach, data were collected through interviews, documentation, and field observations. The findings reveal that the restaurant and entertainment sectors dominate PBJT revenue, while parking and street lighting contribute minimally. Digital reporting through the Atraksi PD application, audit sampling, and taxpayer outreach have enhanced compliance and transparency. Nevertheless, challenges such as low taxpayer compliance and discrepancies in reported income continue to impede optimal revenue performance. Strengthening digital supervision and targeted compliance interventions is essential to improve PBJT governance and support sustainable regional fiscal capacity.